2012
DOI: 10.1007/s00595-012-0127-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplantation lymphoproliferative disorder in living-donor liver transplantation: a single-center experience

Abstract: Although PTLD is potentially life-threatening, it can be managed by appropriate and prompt treatment, with a good outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In contrast, PTLD incidence is about 4% after hematopoietic stem cell transplant (HSCT) [ 9 ]. Historically, mortality rates in SOT-related PTLD were 50–70% and up to 70–90% in HSCT, although recent data suggests that outcomes have been improving and comparable to SOT [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, PTLD incidence is about 4% after hematopoietic stem cell transplant (HSCT) [ 9 ]. Historically, mortality rates in SOT-related PTLD were 50–70% and up to 70–90% in HSCT, although recent data suggests that outcomes have been improving and comparable to SOT [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently, a few comprehensive studies on the characteristics of PTLD have been reported in the Asian population, including research completed by our institution. [3][4][5][6] Unfortunately, to our knowledge, there are no large systemic reviews of the correlation between PTLD and whole blood EBV DNA levels in Korean organ recipients.…”
mentioning
confidence: 99%
“…However, these risk factors may reflect center effects. 5 Treatment for recurrent acute rejection also puts patients at risk for PTLD. The risk of symptomatic EBV infection and PTLD is greater in patients with more than 1 rejection episode in the first year after transplant.…”
Section: Pathologymentioning
confidence: 99%